2012
DOI: 10.1007/s10725-012-9681-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser light treatment on some biochemical and physiological processes in seeds and seedlings of white lupine and faba bean

Abstract: The aim of present study was to determine the changes of some biochemical and physiological processes, which occurred in seeds and seedlings of white lupine and faba bean after pre-sowing treatment with laser beams. It was found this treatment of seeds considerably increased the activity of amylolytic enzymes in seeds of both plants. The greatest differentiation of the enzymatic activity was noticed after 120 h from the time of sowing but the activity of these enzymes in the seeds of both tested plants was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 12 publications
4
33
0
7
Order By: Relevance
“…However, according to some authors, the best method to combine these goals is the use of physical treatments (Delibatowa and Ivanova, 2006;Flórez et al, 2007;Hernandez et al, 2010;Jun et al, 2007;Rochalska and Orzeszko-Rywka, 2008). In some researches opinion, presowing physical treatments of seeds are environmentally safe because they only modify biochemical and physiological processes in seeds, which, in consequence, accelerate seedling emergence and improve plant development (Chen et al, 2005a;Podleśny et al, 2012;Rubinov, 2003). Physical treatments, such as laser irradiation, do not replace chemical methods, but they can supplement them (Ouf and Abdel-Hardy, 1999;Vasilevski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to some authors, the best method to combine these goals is the use of physical treatments (Delibatowa and Ivanova, 2006;Flórez et al, 2007;Hernandez et al, 2010;Jun et al, 2007;Rochalska and Orzeszko-Rywka, 2008). In some researches opinion, presowing physical treatments of seeds are environmentally safe because they only modify biochemical and physiological processes in seeds, which, in consequence, accelerate seedling emergence and improve plant development (Chen et al, 2005a;Podleśny et al, 2012;Rubinov, 2003). Physical treatments, such as laser irradiation, do not replace chemical methods, but they can supplement them (Ouf and Abdel-Hardy, 1999;Vasilevski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of He-Ne laser on plants has recently received attention this led to various investigations (Qiu et al, 2010(Qiu et al, & 2013Podleśny et al, 2012;Abu-Elsaoud and Tuleukhanov, 2013;Jamil et al, 2013;Jia and Duan, 2013;Abu-Elsaoud, 2013& 2015 . Nevertheless, these previous investigations have not focused on the damage repair role of laser on photosynthesis under ultraviolet radiations stress.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 generated during the conversion of O 2 − can be further eliminated by POD and other antioxidants (Apel and Hirt 2004). It has been reported that laser irradiation could enhance enzyme activities of seeds and plants (Chen et al 2005a;Jamil et al 2013;Podlesny et al 2012). Therefore, increasing SOD and POD activities under laser irradiation could be a strategy to protect cells from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%